Persepsi Akuntan Pendidik dan Mahasiswa Akuntansi Terhadap Kode Etik Akuntan Indonesia - Suhaji, Suhaji; Sugiarti, Lilik (Jurnal Ilmiah Aset, 2008)
This research is to know the perception of academic accountant and accounting student about Indonesia Accountant ethics at the colleges in Semarang. Data is submitted form 32 accountants and 72 accounting students at 7 universities. The result of this research is that academic accountants and accounting student have positive perceptions about Indonesia accountant ethics by the most of answer who agree with the positive statement and disagree with the negative statement and there siginificant difference between the perception of academic accountants and accounting students about Indonesia accountant ethics at the colleges in Semarang.